Carbon Pricing Influences Competition — and Benefits From It - Johannes Paha (Wirtschaftsdienst)
Abstract This article studies the interaction effects between climate change policies, especially German and European emission trading schemes, and competition. It demonstrates why the effectiveness of those policies is diminished in markets characterized by market power, and how antitrust laws can improve this situation. Emissions trading may also reduce the competitiveness of German and European companies internationally. In response, there have been calls for its modification, which may, however, cause subsidy races and tax competition. State aid control as an element of European competition policy, world trade law and climate diplomacy counteract these effects.